INSTITUTIONALIZATION OF PERSONALISM: INSTITUTE OF THE NATION’S LEADER IN THE POST-SOVIET SPACE - BORISOV, Nikolay (CENTRAL ASIA AND THE CAUCASUS, 2017)
In today’s post-Soviet states of Central Asia, the political transformations have led to the traditionalization of political life and revival of conventional political institutions. It is noteworthy that the informal political institutions received a formal status in a number of states. The article deals with the formation and legislative regulation of the institute of the Nation’s Leader in Turkmenistan, Kazakhstan, and Tajikistan, in terms of identifying the general and particular reasons for the emergence of the institute, functioning results, and the prospects for its development. The main factor in the formalization of the institute of the Nation’s Leader in the analyzed countries is the weakness of traditions of the national statehood and the low level of national identity, understood as a civil-political identity. The specificity of institutionalization of the institute of the Nation’s Leader lies in the fact that the informal practice of a personalistic type of domination is transformed into political and legal institutions, while legislative norms govern the legal relations connected with the status of a particular individual. A high level of institutionalization of personalistic presidency is considered by the ruling elites of the analyzed countries as the main basis for political stability and sustainable legitimation of the political regimes. The implementation of the forthcoming transfer of power in these countries is likely to confirm these expectations.